RNA-seq Profiling Reveals Defense Responses in a Tolerant Potato Cultivar to Stem Infection by Pectobacterium carotovorum ssp. brasiliense - Kwenda, Stanford; Motlolometsi, Tshepiso V.; Birch, Paul R. J.; Moleleki, Lucy N. (Frontiers in Plant Science, 2016)
Pectobacterium carotovorum subsp. brasiliense is a member of the soft rot Enterobacteriaceae (SRE) family that causes tuber soft rot and blackleg diseases of stems in potato plants. Currently, there are no effective chemical strategies for the control of members of the SRE. Thus, an understanding of the inducible defense responses in stems of potato plants is important, particularly during colonization of the vascular system. Here, time-course RNA-sequencing analysis was used to compare expressed genes between a susceptible potato cultivar (Solanum tubersoum cv Valor) and a tolerant cultivar (S. tuberosum cv BP1) at 0, 6, 12, 24, and 72 h post-inoculation with P. c. brasiliense. In total, we identified 6,139 and 8,214 differentially expressed genes (DEGs) in the tolerant and susceptible cultivars, compared to mock-inoculated controls, respectively. Key DEGs distinguishing between tolerance and susceptibility were associated with negative regulation of cell death and plant-type cell wall organization/ biogenesis biological processes in the tolerant and susceptible cultivars, respectively. Among these were DEGs involved in signaling (mainly MAPK cascade and ethylene pathway), defense-related transcription regulation including WRKY transcription factors, and downstream secondary cell biosynthesis. Together, our results suggest that S. tuberosum cv BP1 likely employs quantitative defense response against P.c brasiliense. Overall, our study provides the first transcriptome-wide insight into the molecular basis of tolerance and/or resistance of potato stems to SRE infection.